Prospective study of intraoperative and post-operative complications during laparoscopic cholecystectomy among patients presenting with acute calculous cholecystitis - Rajat Kumar; Chandrakala; Ritu Kumari Saxena; Shirale , Vaishali (Asian Journal of Medical Sciences, 2023)
Background: Acute cholecystitis was initially thought to be a contraindication for laparoscopic cholecystectomy. Now, as the experience is increasing, laparoscopic surgeons are gradually undertaking laparoscopic cholecystectomy as the preferred procedure even in an acute setting. Early surgery in acute presentation has better surgical outcome with lesser and cheaper hospital stay and predictive of better quality of life as compared to delayed treatment. Aims and Objectives: The objectives of this study were to study the perioperative complications during early laparoscopic cholecystectomy. Materials and Methods: One hundred and five patients with acute calculus cholecystitis visiting Fortis Escorts Hospital, Faridabad from June 2017 to November 2018 were studied. All patients underwent laparoscopic cholecystectomy and subsequently compared for the following intraoperative parameters: Presence of adhesions, calot’s anatomy, need for decompression of gallbladder, difficulty in dissecting the gallbladder from liver bed, retrieval of gallbladder, time taken to complete surgery, need of placement of drain, and need for conversion to open cholecystectomy. Complications studied were massive bleed, bile spillage during dissection, stone spillage, duodenal injury, and common bile duct [CBD] injury. Results: Decompression of the acute inflamed gallbladder facilitates laparoscopic cholecystectomy in acute cholecystitis with low conversion rate of 2.86%. Bleeding, CBD injury and duodenal injury are uncommon complications but major factors for conversion. Conclusion: Most common reasons for difficulty in laparoscopic cholecystectomy for acute cholecystitis were found to be adhesions in Calot’s triangle and adhesion of gallbladder with surrounding structures (duodenum/transverse colon).